GIS-based overlay analysis of flood hazard and settlement exposure in Bandar Lampung City - Amjad Malik Perdano; Ahmad Rowatul Irham (Priviet Social Sciences Journal, 2026)
Flooding is one of the most frequent hydrometeorological disasters in Indonesia, with increasing intensity due to climate change, rapid urbanization, and inadequate drainage systems. Bandar Lampung City has experienced a significant rise in flood events, affecting thousands of households and expanding into densely populated residential areas. This study aims to analyze the spatial distribution of flood hazards and their relationship with settlement areas using a Geographic Information System (GIS)-based overlay method. Flood hazard data were obtained from InaRISK (2025), while settlement data were derived from Ina-Geoportal (2022). The overlay analysis was combined with a scoring method to classify hazard levels into low, medium, and high categories. The results indicate that flood-prone areas cover 3,225.69 ha, dominated by the medium hazard class. Settlement areas affected by flood hazards reach 1,539.14 ha, with the majority falling into the medium hazard category. Sub-districts such as Sukarame, Tanjung Senang, and Kedamaian show the highest exposure of settlements to flood hazards. These findings highlight that urban development patterns and land-use changes significantly influence flood vulnerability. Therefore, integrating flood risk considerations into spatial planning and improving drainage systems are essential to reduce potential impacts and support sustainable urban development.